The use of social media as a source of religious knowledge among doctors in Makassar, Indonesia - Mahmuddin; Abdul Halik (Penerbit Universiti Kebangsaan Malaysia, 2019)
In the past, religious knowledge was obtained by reading religious books, but now the development of technology allows religious knowledge to be obtained from social media instead. This article aims to determine the use of social media as a source of religious knowledge for doctors in Makassar, Indonesia. The method used is qualitative, conducted through observations and in-depth interviews with key informants, i.e. members of this social group. Participants were recruited via a local Whatsapp group that contained 66 doctors, 15 of which then became informants in this study. The results of the study show that Facebook, WhatsApp, and Instagram are the most widely used forms of communication media for doctors to obtain religious knowledge. Furthermore, the majority of the religious messages posted in the WhatsApp social group by these health center doctors is for daily instructions and is posted according to the needs of members. The doctors usually do not give many comments on the messages in their social groups to avoid differences of opinion or conflicts between members. If there is a message that may lead to different opinions or even debate, mutual respect becomes their first consideration, because they realize that mutual respect is necessary when living in such a multicultural, multi-ethnic, and multi-religious society. The implications of this research are an increased awareness of how communication media works and an understanding that the mosque is not the only way we can develop and increase our religious knowledge.